De líderes históricos à opositores : as dissidências republicanas e o jogo político regional (Rio Grande do Sul, 1890-1907) - Saccol, Tassiana Maria Parcianello (2018)
This thesis aims to analyze how some of the main divisions of Rio Grande – Republican Party take place. Taking as its object the first and second great dissidents – which occurred, respectively, in 1890/91 and 1907 – we seek to evaluate which motivations led to the rupture of leaders with the party and, thus, what was being effectively disputed in each of these conjunctures of party and political play. The individual journeys of some of the main dissidents were the guiding thread of our investigation. From the identification of the debates and episodes in which each one of these individuals were involved, the insufficiency of the explanations based on supposed ideological rivalries could be verified, proposing, in contrast, disputes over personal interests and spaces of power as a common motive for these dissidents. The empirical material researched consists mainly of press editorials and private correspondences, works based on an approach that favors notions as faction and chain of leader-followers, and which aims to better understand the logics pertaining to Rio Grande do Sul politics of the late nineteenth and early twentieth century.